The influence of emotional intelligence on diversity complexity cognition and the attitude towards diversity - J. M. Kamps; A. S. Engelbrecht (South African Journal of Business Management, 2011)
The aim of the study was to develop and validate a theoretical model explicating the structural relationships between diversity complexity cognition, emotional intelligence and a positive attitude towards diversity in the South African business context. The sample selected for the study consisted of 237 employees from various South African organisations. The content and structure of the latent variables were investigated by means of item analysis, as well as confirmatory and exploratory factor analysis. The results of structural equation modelling (SEM) demonstrated good model fit for the refined measurement models and the structural model. A positive relationship was found between emotional intelligence and the latent variables of valuing individual differences and positive perceptual depth. The practical implications were highlighted to ultimately inform management seeking to build an ethically diverse and productive workforce that values the individuality of others.
Keywords: 650